The Effect of The Illustration Program on Fashion Design Inspired by Historical Costumes: تهاني ناصر العجاجي -هدى عبد العزيز المقرن (Al-Academy, 2019)
This research aims to identify the role and impact of illustrations in contemporary fashion design inspired by historical costumes. Historical fashion aesthetics are adapted to design drawings. The experimental method was followed and a sample of 31 students in the department of fashion and textile design, third level were selected. Each student carried out two original historical and contemporary design. The models were executed two times: one with the usage of the program and the other without program help. The tools that were used are the program, the scale, the pre-skill test, and the post-skill test. One of the most relevant results of the research is the possibility of using historical costumes to highlight creativity and innovation in fashion illustrations. There are statistically significant differences between the pre-test and post-test of the sample of the research in historical costumes.There are also statistically significant differences between pre-design and post- design in the same research sample. One of the most important recommendations is to link the illustrations course with the history of fashion in academic programs specialized in fashion design, conduct more studies and scientific research in the field of fashion design, and encourage Saudi fashion designers to innovate in the design of contemporary fashion inspired by historical fashion